An experimental and numerical study of chemically enhanced water alternating gas injection - Majidaie, S. (China University of Petroleum Beijing, 2015)
In this work, an experimental study combined with numerical simulation was conducted to investigate the potential of chemically enhanced water alternating gas (CWAG) injection as a new enhanced oil recovery method. The unique feature of this new method is that it uses alkaline, surfactant, and polymer additives as a chemical slug which is injected during the water alternating gas (WAG) process to reduce the interfacial tension (IFT) and simultaneously improve the mobility ratio. In essence, the proposed CWAG process involves a combination of chemical flooding and immiscible carbon dioxide (CO2) injection and helps in IFT reduction, water blocking reduction, mobility control, oil swelling, and oil viscosity reduction due to CO2 dissolution. Its performance was compared with the conventional immiscible water alternating gas (I-WAG) flooding. Oil recovery utilizing CWAG was better by 26Â of the remaining oil in place after waterflooding compared to the recovery using WAG conducted under similar conditions. The coreflood data (cumulative oil and water production) were history matched via a commercial simulator by adjusting the relative permeability curves and assigning the values of the rock and fluid properties such as porosity, permeability, and the experimentally determined IFT data. History matching of the coreflood model helped us optimize the experiments and was useful in determining the importance of the parameters influencing sweep efficiency in the CWAG process. The effectiveness of the CWAG process in providing enhancement of displacement efficiency is evident in the oil recovery and pressure response observed in the coreflood. The results of sensitivity analysis on CWAG slug patterns show that the alkalineâsurfactantâpolymer injection is more beneficial after CO2 slug injection due to oil swelling and viscosity reduction. The CO2 slug size analysis shows that there is an optimum CO2 slug size, around 25Â pore volume which leads to a maximum oil recovery in the CWAG process. This study shows that the ultralow IFT system, i.e., IFT equaling 10â2 or 10â3 mN/m, is a very important parameter in CWAG process since the water blocking effect can be minimized. Â© 2015, The Author(s).